Prisoners on the Great White Way: Short Eyes and Zoot Suit as the First US Latina/o Plays on Broadway - Lucas, Ashley (Latin American Theatre Review, 2010)
The first two Latina/o-written and directed plays on Broadway were Miguel Piñero’s Short Eyes in 1974 and Luis Valdez’s Zoot Suit in 1979. Both plays use Latino prisoners as their central characters. Though the reception of the two plays in the popular press differed, with Short Eyes receiving glowing praise and Zoot Suit largely dismissed, the critics used the same rubric to judge them: the plays were overtly evaluated in terms of received notions of cultural authenticity and criminality. Ultimately, the commercial success of Short Eyes and Zoot Suit’s failure on Broadway both had to do with the ways in which New York criticsregistered the playwrights’ differing representations of racialized criminality. (AL, Article in English)